Microstructured BN Composites with Internally Designed High Thermal Conductivity Paths for 3D Electronic Packaging (Adv. Mater. 38/2022). Issue 38 (23rd September 2022) - He, Hongying; Peng, Weixiang; Liu, Junbo; Chan, Xin Ying; Liu, Shike; Lu, Li; Le Ferrand, Hortense
Abstract : Heat Transfer In article number 2205120, Hortense Le Ferrand and co‐workers present a high‐thermal‐conductivity BN‐based composite with locally oriented microstructures that can conduct heat intentionally toward specific areas. The customizable heat‐transfer paths highlight a solution for thermal management of future 3D integrated electronics.